KOLAM BUNDAR DENGAN SISTEM DRUM - Sutrisno Sutrisno (Universitas Merdeka Madiun, 2022)
The type of cultivation that will be developed is an enlargement business with catfish commodities. Catfish was chosen as a commodity to be developed because this type of fish is easier in terms of marketing, harvest time is faster and maintenance is easier, if in practice applying good fish farming methods accompanied by appropriate management and technology. The method used is the use of iron trellis as a medium to support the load and tarpaulin as a water retaining pad. The model imitated is the drum principle, making it easier to maintain cleanliness and save water. The water contained in the pool, when it is about to be cleaned, is not all thrown away. The water that is discharged is only the bottom of the pool or the bottom of the pool. Water at the bottom or bottom of the pool that contains dirt deposits. The results obtained are the ease of making ponds, maintenance, filling water, and saving water with an open and close faucet system at the bottom.